Employment growth, inflation and output growth: Was Phillips right? Evidence from a dynamic panel - Guglielmo Maria Caporale; Marinko Škare (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
In this paper we analyse the short- and long-run relationship between employment growth, inflation and output growth in Phillips' tradition. For this purpose we apply FMOLS, DOLS, PMGE, MGE, DFE, and VECM methods to a nonstationary heterogeneous dynamic panel including annual data for 119 countries over the period 1970-2010, and also carry out multivariate Granger causality tests. The empirical results strongly support the existence of a single cointegrating relationship between employment growth, inflation and output growth with bidirectional causality between employment growth and inflation as well as output growth, giving support to Phillips' Golden Triangle theory.
Keywords: C23; E24; E31; E60; 330; employment growth; inflation; output growth; Golden Triangle theory; Phillips-Kurve; Beschäftigung; Inflation; Wirtschaftswachstum; Panel; Schätzung; Welt